Nursing of acupoint injection therapy combined with intravenous administration of antiemetics in the treatment of nausea and vomiting in a patient with paclitaxel liposome chemotherapy (穴位注射疗法联合静脉滴注止吐药治疗紫杉醇脂质体化疗后恶心呕吐1例的护理体会) - LIU Fei (刘菲); LIU Shuhong (刘书红); ZHAO Yanan (赵亚楠) (中西医结合护理)
This article summarizes the nursing experience of a patient with nausea and vomiting after paclitaxel liposome chemotherapy treated by acupoint injection therapy combined with intravenous administration of antiemetic drugs. Comprehensive nursing interventions on hospitalization environment, dietary and emotion of the patient were carried out. Based on the Traditional Chinese Medicine meridian theory, Zusanli acupoint injection of metoclopramide combined with intravenous drips of ondansetron was administrated to relieve the nausea and vomiting symptoms and improve the gastrointestinal function of the patient during chemotherapy. (本文总结穴位注射疗法联合静脉滴注止吐药治疗1例紫杉醇脂质体化疗后患者恶心呕吐的护理经验。基于中医经络学说理论, 在环境护理、饮食护理、情志护理等常规基础上, 采用足三里穴位注射甲氧氯普胺联合静脉滴注昂丹司琼镇吐止呕, 快速缓解患者恶心呕吐症状, 改善患者胃肠功能。)